Proposal and analysis of carbon nanotube based differential multibit through glass vias. (August 2022) - Kumar, Ajay; Chandel, Rajeevan; Dhiman, Rohit
Abstract: The paper proposes glass as a potential material to advanced interposers for high-density three-dimensional (3-D) integration. On the basis of multi-bit through glass via (TGV) which comprises of TGVs filled with multi-walled carbon nanotubes (MWCNTs)/single-walled CNTs (SWCNTs) and separate conducting pads, the design of novel differential multibit-CNT TGVs (DM-TGCVs) is proposed and studied. The effective complex conductivity is formulated for accurate characterization of the high frequency behaviour of DM-TGCVs. A distributed π-type transmission line model for the modeling of DM-TGCVs is established and the frequency dependent impedance is extracted through partial element equivalent circuit (PEEC) technique. The influence of CNT filling ratio, probability of metallic fraction of CNTs, and CNTs as filler material on the resistance and inductance is also studied. Through the proposed analytical model, signal insertion loss of DM-TGCVs in the differential- and common-mode configurations is exhaustively investigated. Due to ultra-high electrical resistivity of glass (10 12 − 10 16 Ω-cm), signal loss in DM-TGCVs is determined by the conductor loss, which results in an improved electrical performance under differential-mode signaling than common-mode signaling approach. This phenomenon is unique to TGVs and totally different from the conventional through silicon vias, where signal loss is dominated by the dielectric loss at high frequencies. The magnitude of insertion loss ( S 21 ) for the proposed DM-TGCVs under differential-mode configuration w.r.t. differential TSVs (D-TSVs) and differential multibit CNT TSVs (DMC-TSVs) improves up to ∼ 44% and ∼22%, respectively for varying via radius. The DM-TGCVs also exhibit superior crosstalk inhibition capability and provide up to ∼89% and ∼24% improvements in crosstalk than D-TSVs and DMC-TSVs at f = 20 GHz. More importantly, DM-TGCVs provide one-third saving of the chip area compared to D-TSVs.